O processo de ensino aprendizagem da libras por jovens surdos através dos sinais dialetais - Silveira, Briele Bruna Farias da (2017)
In this study, we identified and described the signs brought by three deaf people from rural communities who are assisted by the Rural Training Center - Specialized Care Center (CRF-CAE), located in the Cruz do Espírito Santo City - PB. In order to investigate these signs, both common to all deaf and variable, we are based on the sociolinguistic perspective, which considers language as a social institution (WEINREICH, LABOV, HERZOG, 1968; LABOV, 1975). However, we discussed language and social interaction (SAUSSURE, 1975; MARTELOTTA, 2013; GÓES, 2002) and the acquisition of sign language (QUADROS, 1997; LANGEVIN, 1995). After the analysis of the signs, we worked with three didactic sequences, using them in the teaching-learning process of the Brazilian Sign Language - LIBRAS, the first two sequences being from instructional texts and the third, from cordel literature. The results show that the signs developed by the deaf within the family, in addition to being linguistically structured, are subject to extralinguistically motivated variation, which accredits them to have the status of dialectal signs. They demonstrated, mainly, that the teachinglearning of an official sign language, mediated by the dialectal signal, is fundamental to the process. We hope, therefore, that this study may serve as a basis for other works with a similar purpose.